A COMPARATIVE STUDY ON THE EFFECT OF USING PQ4R AND ETR STRATEGIES ON STUDENTS’ READING COMPREHENSION AT SMP PLUS TERPADU PEKANBARU - Nugrahayu, Rizky (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
The aim of this study is to investigate the comparison of Preview, Question, Read, Reflect, Recite and Review (PQ4R) and Experience-Text-Relationship (ETR) strategies on Students’ Reading Comprehension. The research design was quasi-experimental by comparing two strategies, and two experimental groups with pre-test and post-test design. This research involves 64 participants which consisted of 32 students from experimental group 1 and experimental group 2 at SMP Plus Terpadu Pekanbaru. There were 3 research questions with 3 hypothesis proposed in this research in order to identify the significant difference between the effect of using PQ4R and ETR Strategies on students’ reading comprehension. Pre-test and post-test were administered in this study to two experimental groups. Independent sample t-test and paired sample t-test were used to analyzed the data. he research finding indicated that there was no significant difference of post-test mean score between an experimental group 1 which was taught by using PQ4R and ETR Strategies on students’ reading comprehension. The contribution of PQ4R strategy to improve students’ reading comprehension was 83% while ETR strategy was 85%. Finally, it can be concluded that both PQ4R and ETR Strategies can be implemented in improving Students’ Reading Comprehension at SMP Plus Terpadu PekanbaruKeyword: Reading Comprehension, PQ4R Strategy, ETR Strategy.